Severe Preeclampsia at 26 weeks gestation on Nulliparous with complication of Bilateral Serous Retinal Detachment - Winty Septiani; Defri Defri; Obdes Maharani Emputri (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran)
Preeclampsia is still one of the leading causes of death and severe maternal morbidity. The rate of incidences range from 5 to 10 % in all pregnancies. Clinical condition in Preeclampsia is increasing blood pressure and proteinuria. Preeclampsia can cause multisystem disorders including visual disruptions. The incidence rate of visual system disruptions is 25 % of patients with severe preeclampsia and 30% of patients with eclampsia. The most common visual complication is hypertensive retinopathy, serous retinal detachment, and cortical blindness. The incidences of serous retinal detachment are approximately 1% in severe preeclampsia and 10% in eclampsia. We report a case of 28 years old nulliparous with severe preeclampsia at 26 weeks gestation, who complained blurred vision, we ran several examinations and bilateral serous retinal detachment was diagnosed. Her visual has significant improvement a few weeks after pregnancy termination.Abstrak Preeklampsia masih menjadi salah satu penyebab utama kematian dan morbiditas maternal.[1] Tingkat insiden preeklampsia berkisar dari 5 hingga 10% pada semua kehamilan.[2] Kondisi klinis Preeklampsia adalah meningkatnya tekanan darah dan proteinuria. Preeklamsia dapat menyebabkan gangguan multisistem termasuk gangguan penglihatan.[3] Tingkat kejadian gangguan sistem penglihatan adalah 25% pada pasien dengan preeklampsia berat dan 50% pada pasien dengan eklampsia.[3] Komplikasi visual yang paling umum terjadi adalah retinopati hipertensi, serous retinal detachment, dan kebutaan kortikal.[4] Insidensi serous retinal detachment sekitar 1% pada preeklampsia berat dan 10% pada eklampsia.[5] Kami melaporkan kasus nulipara berusia 28 tahun dengan preeklamsia berat pada usia kehamilan 26 minggu, yang mengeluhkan penglihatan kabur, dilakukan beberapa pemeriksaan dan bilateral serous retinal detachment ditegakkan. Penglihatan pasien mengalami perbaikan yang signifikan minggu ke-lima setelah terminasi kehamilan.